Codes of Conduct in Organisational Context: From Cascade to Lattice-Work of Codes - Preuss, Lutz (Journal of business ethics, 2010)
Codes of conduct have proliferated not only at company level, but also at supra- and sub-organisational levels. However, the latter have remained an under-researched area within the CSR literature. Hence, this article examined what range of organisational and sub-organisational codes large companies – here the FTSE100 constituent companies – have developed. The article isolated seven different types of organisational and sub-organisational codes, which together with six supra-organisational ones form a lattice-work of intermeshing documents. Such a division of labour between types of codes has two significant implications for CSR practice and research. In terms of corporate practice, an analysis of the content of the organisational and sub-organisational codes indicates that companies seem to enter into generalised commitments in the more visible documents, whereas other aspects, in particular more coercive aspects of CSR, get buried in the lower levels of the code hierarchy. In terms of research methodology, the differentiation between codes highlights that an analysis of codes of conduct alone is insufficient to establish what the CSR approach of a company is. Rather, it is the entire range of codes at organisational and sub-organisational levels that scholars of codes of conduct should be concerned with.